Revisiting Gunung Anyar Mangrove Ecotourism: How Satisfaction Mediates Accessibility, Facilities, and Destination Image - Heryono, Didik; Abidin, Zainal (Jurnal Perikanan Universitas Gadjah Mada, 2025)
Indonesia holds substantial potential in sustainable coastal ecotourism development, including urban mangrove tourism such as Gunung Anyar Mangrove Ecotourism in Surabaya. Despite increasing visitor numbers, the destination still faces challenges in facilities and destination image. This study aims to examine the effect of accessibility, facilities, and destination image on revisit intention, with visitor satisfaction as a mediating variable. A quantitative approach was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM) via WarpPLS 8.0. The results reveal that facilities and destination image significantly influence revisit intention both directly and indirectly through satisfaction. In contrast, accessibility shows a positive but statistically insignificant effect. These findings highlight the importance of enhancing facilities and destination image to improve satisfaction and visitor loyalty. This study contributes to the body of knowledge on tourist behavior in the context of sustainable urban mangrove ecotourism.